A search for the direct detection of dark matter via annual modulation with the full XMASS-I dataset - Mason, A (2021)
Astrophysical observations indicate that the observable matter that forms the stars, planets and life as we know it only constitutes 5% to the total energy density of our universe. Dark matter and dark energy make up the remainder, 26% and 69% respectively. While the nature of dark energy is still largely speculative, gravitational effects of dark matter have been widely observed and place constraints on its nature. Many candidates that could form dark matter have been ruled out over the years due to the lack of astrophysical signatures they would imply or lack of production, annihilation and direct detection signals in experiments or instruments that have sensitivity for these signals.